1989
DOI: 10.1038/jcbfm.1989.83
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Local Cerebral Blood Flow Measured by the Quantitative Autoradiographic [14C]Iodoantipyrine Technique in Freely Moving Rats

Abstract: Summary:The postnatal changes in local cerebral blood flow in freely moving rats were measured by means of the quantitative autoradiographic e 4C]iodoantipyrine method. The animals were studied at 10, 14, 17, 21, and 35 days and at the adult stage. At 10 days after birth, rates of blood flow were very low and quite homogeneous in most cerebral structures except in a few posterior areas. From these relatively uniform levels, values of local ce rebral blood flow rose notably to reach a peak at 17 days in all bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 60 publications
6
37
1
Order By: Relevance
“…A bimodal pattern of the ICBF developmental curve was also observed by Nehlig et al (1989) dur ing postnatal maturation in the rat; this study found that, following an initial peak lCBF at 17 days, a decline in ICBF occurred in many structures between 17 and 21 days, after which there was a sec ond increase in lCBF to reach final adult values. This second increase in lCBF in the rat, however, consisted of a gradual increase from 21 days to ap proach adult values by 35 days.…”
Section: Second Metabolic Peaksupporting
confidence: 60%
See 2 more Smart Citations
“…A bimodal pattern of the ICBF developmental curve was also observed by Nehlig et al (1989) dur ing postnatal maturation in the rat; this study found that, following an initial peak lCBF at 17 days, a decline in ICBF occurred in many structures between 17 and 21 days, after which there was a sec ond increase in lCBF to reach final adult values. This second increase in lCBF in the rat, however, consisted of a gradual increase from 21 days to ap proach adult values by 35 days.…”
Section: Second Metabolic Peaksupporting
confidence: 60%
“…It is probably for this reason that a transient developmental stage of increased ICMRglc over adult values was not de tected in the developing rat in the study by Nehlig et al (1988). More recent studies by Nehlig et al (1989) suggest that measurements of local cerebral blood flow (lCBF) are a better indicator of total ce rebral energy demand in the immature rat than lCMRglc measurements.…”
Section: Methodological Considerationsmentioning
confidence: 83%
See 1 more Smart Citation
“…18,31 Compared with other studies, our CBF values are substantially higher than those reported in unanesthetized neonate rats. 10,31,32 Our methodological CBF procedure can hardly account for the differences, since it is very close to that of Nehlig et al 31 Basal hypercapnia found in P7 rats (62.4 ± 5.0 mm Hg), compared with juvenile (36 ± 2 mm Hg) and adult rats (38 ± 1 mm Hg) could in part explained the enhanced CBF values measured in this study, because arterial CO 2 was reported to increase cerebrocortical red-cell flow under moderate isoflurane anesthesia. 33 The caudorostral gradient of blood-flow rates we found in sham-operated p7 rats is steeper than that reported in other studies.…”
Section: Discussioncontrasting
confidence: 74%
“…The newborn rat, although economical, is so small at birth that it is not possible to catheterize vessels or obtain blood samples necessary to monitor physiologic changes that may influence the cerebral circulation. Nevertheless, techniques for autoradiographic cerebral blood flow measurements have been adapted for rats 7 or 10 d of age (5,6). The newborn lamb and piglet are of an appropriate size for frequent sampling of blood and recording of various physiologic parameters; however, these animals are rather large for extensive autoradiographic studies of cerebral blood flow.…”
mentioning
confidence: 99%